IMPLEMENTATION OF THE COMSTOCK METHOD FOR ANDROID BASED PATIENT LEFTOVERS FOOD MANAGEMENT - lu'luil maknun sundarina (International Journal of Informatics and Computation, 2020)
Nowadays, nutritionists should count manually to know how much nutrition that patients get as the development of technology, human work easier likewise in counting the patient's food waste so it will be more efficient and not waste a lot of time. This research aims to build an application that can facilitate nutritionists in the calculating amount of food waste by using the Comstock method. The system is designed to use Unified Modeling Language (UML) and programming language Hypertext Preprocessor (PHP) and Hyper Markup Language (HTML). The result of this research is in the form of application which could be used by nutritionists at hospital calculate the amount of food waste of patients using the android-based Comstock method at the hospital using the Comstock method.